A workplace-based HIV self-testing intervention as a determinant for self-testing knowledge, beliefs, and use among unskilled workers in Wakiso Uganda - Gerald Mukisa Nsereko; Khamisi Musanje; Eron Robinah Ayesiga; Loyce Kiiza Kobusingye; Rhoda Namubiru; Moses Sempala; Christine Kiwala; Martin Mabunda Baluku (BMC Public Health)
Abstract Background The HIV burden still persists to date, as a public global health challenge despite numerous prevention interventions that have been proposed toward achieving 95% of all people living with HIV aware of their HIV status by 2030. Therefore, this study set out to examine the effect of a workplace-based HIV self-testing intervention on the use of HIV self-testing among unskilled workers in Wakiso Uganda. Methods A quasi-experimental one-group pretest-posttest design was conducted among 46 participants systematically and randomly selected. Data was collected via a validated structured self-administered questionnaire and analysed using the paired samples t-tests and hierarchical multiple regression analysis in SPSS v27. Results A comparison of the mean differences between the pre-post-test scores for the intervention group showed a statistically significant difference for HIVST knowledge [M=-1.38, SD = 0.719, t=-13.0, df = 45, p ≤.05], perceived susceptibility [M=-0.92, SD = 0.867, t=-7.20, df = 45, p ≤.05], perceived benefits [M=-0.92, SD = 0.593, t=-5.63, df = 45, p ≤.05], perceived barriers [M=-1.22, SD = 1.12, t=-5.63, df = 45, p ≤.05], and HIVST use [M=-1.22, SD = 1.12, t=-5.63, df = 45, p ≤.05]. However, it’s noteworthy to state that perceived barriers increased exponentially than earlier hypothesized amidst the knowledge acquired. Multiple regression model showed that HIVST knowledge and individual beliefs predict 37.2% [F(11,34) = 3.485, p ≤.05] of the variance in HIVST use and the overall biggest predictor of HIVST use was perceived susceptibility 53.7% (Beta = 0.537, t = 2.44, p ≤.05). Conclusions Efforts should be directed toward advocating for frequent knowledge sharing about self-testing such as this study has provided among unskilled working populations in Uganda. Organizations, alongside HIV testing implementing partners, should awaken people operating in risky environments and those engaging in risky sexual acts on the threat of succumbing to HIV as this greatly increases HIVST and repeat testing.